Neuroscience of Object Relations in Health and Disorder: A Proposal for an Integrative Model - Svrakic, Dragan M.; Zorumski, Charles F. (Frontiers in Psychology, 2021)
ABSTRACT: Recent advances in the neuroscience of episodic memory provide a framework to integrate object relations theory, a psychoanalytic model of development of the human mind, with potential neural mechanisms. An object relation is a primordial cognitive-affective unit of the mind derived from survival- and safety-level experiences with caretakers during phase-sensitive periods of infancy and toddlerhood. Because these are affect-enhanced learning experiences, their neural substrate likely involves affect-enhanced episodic memories, encoded by the hippocampus-amygdala circuitry and consolidated by medial prefrontal cortex (mPFC). Inaugural self- and object-mental representations, extracted from early experiences, are first dichotomized by contradictory affects evoked by frustrating and rewarding interactions (“partial object relations”). Affective dichotomization appears to be hardwired in the amygdala. Intrinsic propensity of the mPFC to form nonconscious schematic frameworks for episodic memories may pilot integration of dichotomized experience in infancy. With the emergence of working memory, an activated self- and object-representation of a particular valence can be juxtaposed with its memorized opposites creating a balanced cognitive-affective frame (“integrated object relations”). Specific memories of object relations are forgotten but nevertheless profoundly influence the mental future of the individual, acting i) as the implicit schema, formed and stored in mPFC, that regulates the relevance and preferential assimilation of new experience as it is being processed by the hippocampus-amygdala circuits, and ii) as basic units of experience that modulate interactive self-organization of functional brain networks that underlie the mind. A failure to achieve integrated object relations is predictive of poor adult emotional and social outcomes, including personality disorder. Cognitive, cellular-, and systems-neuroscience of episodic memory appear to support key postulates of object relations theory and help elucidate neural mechanisms of psychodynamic psychotherapy. Derived through the dual prism of psychoanalysis and neuroscience, the gained insights may offer new directions to enhance mental health and improve treatment of multiple forms of psychopathology.